Preliminary study of anti-CD40 and ubiquitin proteasome antibodies in primary podocytopaties - Chebotareva, Natalia; Cao, Venzsin; Vinogradov, Anatoliy; Alentov, Igor; Sergeeva, Natalia; Kononikhin, Alexey; Moiseev, Sergey (Frontiers in Medicine, 2023)
Background: The pathogenesis of podocytopathies is not clear and many questions remain to be resolved. The aim of the study is to evaluate the levels of anti-CD40 and anti-ubiquitin carboxyl-terminal hydrolase L1 (anti-UCHL1) antibodies in patients with podocytopathies in comparison with other gloerulopathies. Methods: One hundred and six patients with glomerulopathy and 11 healthy subjects were included in our study. A histological study revealed primary FSGS in 35 patients (genetic cases of FSGS and secondary FSGS in the absence of NS were excluded), 15 had MCD, 21 - MN, 13 - MPGN, 22 patients - IgA nephropathy. Serum levels of anti-UCHL1 and anti-CD40 antibodies were measured by ELISA before steroid treatment. Results: The levels of anti-UCHL1 antibodies were significantly higher in MCD patients and anti-CD40 antibodies were higher in MCD and FSGS than in control group and other groups of glomerulopathies. In addition, in patients with steroid-sensitive FSGS and MCD, the level of anti-UCHL1 antibodies was higher, and anti-CD40 antibodies were lower than in patients with steroid-resistant FSGS. An increase in anti-UCHL1 antibody levels above 6.44 ng/ml may be a prognostic factor of steroid-sensitivity. The ROC curve (AUC = 0.875 [95% CI 0.718-0.999]) for response to therapy showed the sensitivity of 75 % and specificity of 87.5 %. Conclusions: An increase in the level of anti-UCHL1 antibodies is specific for steroid-sensitive FSGS and MCD, while an increase in anti-CD40 antibodies – for steroid-resistant FSGS, compared with other glomerulopathies.